Innovation of English language teaching mode in basic education under the integration of information technology - Zhang, Jianfang; Lu, Junbiao (Edelweiss Applied Science and Technology, 2025)
With the continuous development of information technology, English language teaching in basic education faces new opportunities and challenges. It is challenging to satisfy the demands of individualized learning and interactive communication with the current English teaching model, which has the issue of a gap between conventional instructional techniques and student requirements. To this end, this paper introduces the integration of information technology and education and teaching to explore innovative English language teaching models. By using multimedia, the Internet, and artificial intelligence technologies, a student-centered and highly interactive teaching platform is constructed to stimulate students' learning interest and improve learning outcomes. This paper specifically analyzes the application of information technology in English language teaching and proposes an innovative model based on intelligent auxiliary teaching, network resource sharing, data analysis, and feedback. The results show that the average class time of students in the experimental group is 16.2 hours, while the average class time of students in the control group is only 12.0 hours. After the integration of information technology, students' language application ability and autonomous learning ability have been significantly improved, classroom interactivity and learning outcomes have been effectively enhanced, and teachers' teaching quality and efficiency have also been improved.